Berbagai Dosis Kombinasi Limbah Pabrik Kelapa Sawit (LPKS) dengan Limbah Ternak Sapi (LTS) terhadap Pertumbuhan Vegetatif Jagung Manis (Zea mays Saccharata Struth) - Akhmad Rifai Lubis; Meriksa Sembiring (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The research has been carried out in Sei Mencirim Village, Sunggal District, Deli Serdang Regency, with an altitude of ± 400 meters above sea level, carried out from April to September 2019, with the title “Combination of Palm Oil Mill Waste (POMW) with Cow Cattle Waste (CCW) and Specific Doses Affect the Vegetative Growth of Sweet Corn (Zea mays saccharata struth)”. This research used factorial randomized block desigan (RBD). Factor I LPKS combination : LTS symbol (P) consists of P1 (70 % Solid : 30 % Solid), P2 (50 % Solid : 50 % Solid), P3 (70 % Solid : 30 % Liquid), P4 (50 % Solid : 50 % Liquid), P5 (70 % Liquid : 30 % Solid), P6 (50 % Liquid : 50 % Solid), P7 (70 % Liquid : 30 % Liquid) and P8 (50 % Liquid : 50 % Liquid). Factor II Dosage (tons/ha) consist of control (DO), 5 tons/ha (D1), 10 tons/ha (D2) and 15 tons/ha (D3) with 32 combinations treatments and 2 replication. The results of research conducted with different combinations of LPKS with LTS with several doses have a significant effect on the vegetative of sweet corn. When to get the best plant height growth is to use a combination of 50 % LpPKS with 59 % LpTS at a dose of 15 tons/ha, while for stem diameter and leaf area is 10 tons/ha.